Effectiveness of interventions to promote healthy diet in primary care: systematic review and meta-analysis of randomised controlled trials - Bhattarai, Nawaraj (BioMed Central, 2013)
BACKGROUND: A diet rich in fruit, vegetables and dietary fibre and low in fat is associated with reduced risk of chronic disease. This review aimed to estimate the effectiveness of interventions to promote healthy diet for primary prevention among participants attending primary care. METHODS: A systematic review of trials using individual or cluster randomisation of interventions delivered in primary care to promote dietary change over 12 months in healthy participants free from chronic disease or defined high risk states. Outcomes were change in fruit and vegetable intake, consumption of total fat and fibre and changes in serum cholesterol concentration. RESULTS: Ten studies were included with 12,414 participants. The design and delivery of interventions were diverse with respect to grounding in behavioural theory and intervention intensity. A meta-analysis of three studies showed an increase in fruit consumption of 0.25 (0.01 to 0.49) servings per day, with an increase in vegetable consumption of 0.25 (0.06 to 0.44) serving per day. A further three studies that reported on fruit and vegetable consumption together showed a pooled increment of 0.50 (0.13 to 0.87) servings per day. The pooled effect on consumption of dietary fibre, from four studies, was estimated to be 1.97 (0.43 to 3.52) gm fibre per day. Data from five studies showed a mean decrease in total fat intake of 5.2% of total energy (1.5 to 8.8%). Data from three studies showed a mean decrease in serum cholesterol of 0.10 (-0.19 to 0.00) mmol/L. CONCLUSION: Presently-reported interventions to promote healthy diet for primary prevention in primary care, which illustrate a diverse range of intervention methods, may yield small beneficial changes in consumption of fruit, vegetables, fibre and fat over 12 months. The present results do not exclude the possibility that more effective intervention strategies might be developed.